Avaliação biológica e de fatores gênicos modulados pelos retinóides no ciclo celular, proliferação, diferenciação, apoptose e necrose em células de cripta intestinal de rato - Freitas, Rosa Elayne Marques de (2014)
Infant mortality affects millions of children around the world and malnutrition contributes about one third of this mortality. Vitamin A is already used in the treatment of childhood malnutrition. However, few or no study has been done, carried out at the cellular level, to assess the impact of vitamin A supplementation in intestinal epithelial cells under in vitro protein malnutrition. Thus, we aimed to demonstrate the effects of malnutrition and treatment with retinoids in the processes of proliferation, apoptosis/necrosis, cell cycle and cell differentiation as well as activation of signaling pathways in IEC-6 rat cells under protein malnutrition. We demonstrated that malnutrition decreased cell proliferation in periods of 6, 12, 24 and 48 hours. In addition, retinyl palmitate treatment intensified the decrease of cell proliferation when compared to the malnourished group in the periods of 24 and 48 hours after supplementation. However, the reduction in proliferation was not related to cell death. Indeed, retinyl palmitate reduced apoptosis in the period of 48 hours after induction of malnutrition. Additionally, malnutrition stimulated cell quiescence, and the same was enhanced by retinol, which was identified by the increase in the percentage of cells in G0/G1 phase and the reduction of the percentage of cells in S phase and G2/M, especially in periods of 24 and 48 hours. To check if malnutrition, with or without supplementation of retinoids, was stimulating cell differentiation, we evaluated the gene transcription of the specific markers FABP and IAP within 42 hours. Both retinoids tested increased approximately 5-fold the expression of FABP and IAP mRNAs. Knowing that differentiation had been stimulated, we decided to check which intracellular signaling pathways, coupled to the activation of G proteins, were activated. Our results demonstrated that protein malnutrition decreased gene transcription of c-Jun, STAT3, MEF2C and ATF2, but increased the expression of the GLI-3 and c-Fos mRNAs in relation to the nourish group. However, retinoids increased the transcription of ELK-1, SRF, c-Jun, FOXO, STAT3, ATF2, GLI-3, NF-kB in relation to the malnourished group. Thus, this study showed that cell malnutrition interfered with cell proliferation stimulating cell quiescence. However, retinoids treatment intensified cell quiescence, decreased IEC-6 apoptosis and stimulated cell differentiation associated with the activation of the molecular pathways of ATF2, MAPK/ERK/JNK, IL-6, Hedgehog, PI3K/AKT and NF-kB.